2010
DOI: 10.1007/s11103-010-9655-y
|View full text |Cite|
|
Sign up to set email alerts
|

Two O-methyltransferases involved in the biosynthesis of methoxypyrazines: grape-derived aroma compounds important to wine flavour

Abstract: Methoxypyrazines (MPs) are volatile, grape-derived aroma compounds that contribute to the distinct herbaceous characters of some wines. Although the full pathway leading to MP production has not been elucidated, there is strong evidence that the final step involves the methylation of non-volatile hydroxypyrazine (HP) precursors. Two cDNA encoding O-methyltransferases (OMTs) that have homology to an enzyme previously purified and shown to catalyse the methylation of HPs were isolated from Cabernet Sauvignon. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
147
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(165 citation statements)
references
References 44 publications
7
147
0
2
Order By: Relevance
“…This trend was in good agreement with that described in previous reports (Ryona et al, 2008;Dunlevy et al, 2010). Similar levels of IBMP were observed in Cabernet Sauvignon grapes from the Huailai and Changli areas, and their highest contents were 129.9 ng/L and 130.6 ng/l respectively.…”
Section: Development Of Mps In Cabernet Sauvignon Grapessupporting
confidence: 92%
See 1 more Smart Citation
“…This trend was in good agreement with that described in previous reports (Ryona et al, 2008;Dunlevy et al, 2010). Similar levels of IBMP were observed in Cabernet Sauvignon grapes from the Huailai and Changli areas, and their highest contents were 129.9 ng/L and 130.6 ng/l respectively.…”
Section: Development Of Mps In Cabernet Sauvignon Grapessupporting
confidence: 92%
“…In Vitis vinifera grapes, MPs accumulate at pre-véraison and then decrease markedly until maturity (Ryona et al, 2008;Dunlevy et al, 2010). The contents of MPs in grapes are affected by cluster light exposure, yield, irrigation condition, vine training, plantation density, seasonal temperature, vineyard altitude and soil (Hashizume & Samuta, 1999;De Boubée et al, 2000;Chapman et al, 2004;Sala et al, 2004Sala et al, , 2005Belancic & Agosin, 2007;Falcão et al, 2007;Ryona et al, 2008;Dunlevy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alignment of the predicted amino acid sequences of CtOMT2 (CtMROMT), CtOMT3 (CtFOMT), CtCAldOMT1, and related OMTs. SAM-biding motifs A, B, and C (Joshi and Chiang 1998); and regions I, II, III, IV, and V are domains conserved among plant OMTs (Dunlevy et al 2010).…”
Section: Sequence Analysis Of Ctomtsmentioning
confidence: 99%
“…The cDNA (DDBJ accession number, AB980250) encodes a polypeptide of 367 amino acids, which is shown in Figure 2 together with other selected OMTs including CtCAldOMT1, CtMROMT, CtFOMT, Forsythia koreana MROMT (FkMROMT) (Ragamustari et al 2014), and M. sativa isoflavone OMT. The Sadenosyl-L-methionine (SAM)-binding motifs A, B, and C (Joshi and Chiang 1998); and domains I, II, III, IV, and V that are conserved among plant OMTs (Dunlevy et al 2010) were present in CtAAOMT (Figure 2). Phylogenetic analysis, which was conducted as previously Umezawa et al 2013) (Figure 3) indicated that the CtAAOMT showed 55% identity to FkMROMT, while it exhibited 49-53% identity to (Dunlevy et al 2010).…”
mentioning
confidence: 99%
“…The Sadenosyl-L-methionine (SAM)-binding motifs A, B, and C (Joshi and Chiang 1998); and domains I, II, III, IV, and V that are conserved among plant OMTs (Dunlevy et al 2010) were present in CtAAOMT (Figure 2). Phylogenetic analysis, which was conducted as previously Umezawa et al 2013) (Figure 3) indicated that the CtAAOMT showed 55% identity to FkMROMT, while it exhibited 49-53% identity to (Dunlevy et al 2010). #, Catalytic residues; *, SAM binding residues; S, Substrate binding residues of Medicago sativa isoflavone OMT (MsIOMT, AAC49927) as determined by Zubieta et al (2001).…”
mentioning
confidence: 99%